2014
DOI: 10.1080/1461670x.2014.886837
|View full text |Cite
|
Sign up to set email alerts
|

You Ain't Seen Nothing Yet

Abstract: PreprintThis is the submitted version of a paper published in Journalism Studies. Citation for the original published paper (version of record):Karlsson, M., Clerwall, C., Nord, L. (2014) You ain´t seen nothing yet.: Transparency' s (lack of ) Effect on Source and Message Credibility. AbstractTransparency has been proposed to both change the way journalism is being produced and increase its credibility. However, little research has been conducted to assess the connection between transparency and credibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
4
42
1
1
Order By: Relevance
“…Since the experiment has already been reported in full elsewhere (Karlsson, Clerwall, and Nord 2014), the main focus in this paper will be on the survey and focus groups with findings from the experiments used supplementarily. The three methods were carried out using the services of Swedish opinion research institute TNS/Sifo.…”
Section: A Multimethods Approach To Study Citizen's Views Of Transparencymentioning
confidence: 99%
“…Since the experiment has already been reported in full elsewhere (Karlsson, Clerwall, and Nord 2014), the main focus in this paper will be on the survey and focus groups with findings from the experiments used supplementarily. The three methods were carried out using the services of Swedish opinion research institute TNS/Sifo.…”
Section: A Multimethods Approach To Study Citizen's Views Of Transparencymentioning
confidence: 99%
“…Thus, when asked to articulate their attitudes towards errors and corrections, respondents will be triggered to report ideal constructs -their own and societal. In our previous experimental study (Karlsson et al, 2014), we found no effect in content or source credibility when a news item was corrected Another strand of research worth further exploration is the stratification and 'net effect' of different kinds of corrections. As our results show, citizens' attitudes towards errors and corrections depend on the level of error and there are more kinds of errors and more nuances to apply than the ones measured in this study.…”
Section: Discussion and Conclusion -The Limited Effect Of Transparencymentioning
confidence: 99%
“…A previous study in an experimental setting (Karlsson, Clerwall & Nord, 2014) found that actual corrections did not have an effect on how citizens evaluated a news item. Thus, there may be a rather large gap between the idealized visions that citizens hold of journalism and the impact of actual journalistic performance on citizens' perceptions of credibility.…”
Section: Accuracy Corrections and The News Audiencementioning
confidence: 99%
See 1 more Smart Citation
“…Just like authenticity, transparency also aims to earn trust. Media transparency means providing an explanation of where the content presented originated, why it was selected and presented as it was (Kovach and Rosenstiel, 2007), and publicising the behind-the-scenes processes that shaped this content (Karlsson et al, 2014).…”
Section: Authenticity Transparency and Trustmentioning
confidence: 99%